Analisis Yuridis Putusan Hakim Dalam Penjatuhan Tindak Pidana Asusila Terhadap Anak - Maku, Anderwati; Darmawati, Darmawati; Nusa, Apriyanto (Jurnal Litigasi Amsir, 2024)
This research focuses on the application of criminal law and judicial considerations in cases of immoral acts against children, as exemplified in Decision Number 53/Pid.sus/2019/PN.Tmt. The study employs normative legal research methods, utilizing library research and analyzing secondary and primary legal materials. The analysis is prescriptive, aiming to assess the correctness or appropriateness of the subject under study according to the law. The Child Protection Law outlines various sanctions for perpetrators of immoral acts against children, often stemming from promiscuity and dating relationships between perpetrators and victims. The study underscores the need for both internal and external monitoring to address morality crimes against children effectively.